ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT PADA BANK MANDIRI REGION V JAKARTA 3 - Shalhan Kurnia; Lindawati Kartika (KOLEGIAL, 2017)
Bank Mandiri as a state-owned bank that continues to be demanded to compete competitively requires good human resources management. To achieve the goals of the organization, Bank Mandiri must have a good level of employee engagement and implementation of organizational culture. The aim of the study was to analyze the perceptions of the employee on the organizational cultures and employee engagement of Bank Mandiri Region V Jakarta 3The data were analyzed by using descriptive analysis and using SEM PLS. The result of descriptive analysis of the perceptions of the employees in Bank Mandiri Region V Jakarta 3 on organizational cultures and employee engagement, indicated that it is considered good implementation. The result of SEM PLS shows that the variables of organizational culture have influences on the employee engagement of Bank Mandiri Region V Jakarta 3. Indicators of organizational culture values and employee engagement aspect that most describe are integrity, customer focus values and vigor aspect.